Complete Genome Sequences of Streptococcus mitis Strains Isolated from the Oral Cavity and Urogenital Tract of a Woman and Her Male Sexual Partner - Mores, Carine R. (Microbiol Resour Announc, 2020)
Streptococcus mitis is a member of the mitis group of the genus Streptococcus, which includes commensal species of the oral cavity and upper respiratory tract. Here, we report 39 complete genome sequences of S. mitis strains isolated from the oral cavity and urogenital tract of a woman and her male sexual partner.